Review on Electrochemical Machining Machine - Nikhil Shinde, Srinivas Chippalkatti, Abhijeet Deshpande, Piyush K. Mathurkar, Vishal B. Ambhore, Rajendra S.Talware (Mathematical Statistician and Engineering Applications, 2023)
The electrochemical machining process is now days considered one of the best machining strategies for micromachining as it has many more benefits over other conventional manufacturing processes like it does not create defective layer after machining, higher material removal rate, easily machined difficult to machine materials, etc. ECM process is also called a non-traditional machining process based on the principle of “electrolysis”. In the present study, a detailed review of different sections of the electrochemical machining process is presented which includes: Ultra-precision motion control for tool positioning, Inter Electrode Gap Control, Electrical Double Layer, design of Power Supply Unit, selection of electrolytes based on the material and its material removal rate, etc. Based on a detailed review of electrochemical micromachining, efforts will be taken to design and developed a novel hybrid setup for electrochemical micromachining machines that will fulfill different industrial needs.